If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -10 = -11 + 9y Reorder the terms: -10 + 12y = -11 + 9y Solving -10 + 12y = -11 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -10 + 12y + -9y = -11 + 9y + -9y Combine like terms: 12y + -9y = 3y -10 + 3y = -11 + 9y + -9y Combine like terms: 9y + -9y = 0 -10 + 3y = -11 + 0 -10 + 3y = -11 Add '10' to each side of the equation. -10 + 10 + 3y = -11 + 10 Combine like terms: -10 + 10 = 0 0 + 3y = -11 + 10 3y = -11 + 10 Combine like terms: -11 + 10 = -1 3y = -1 Divide each side by '3'. y = -0.3333333333 Simplifying y = -0.3333333333
| 3(x-6)/4=4x+6 | | 3(2n+1)+4(n-2)= | | h/2+7=10 | | 1=n/4-1 | | 20=5x+7x^2 | | 14=9-p | | 2+x/5=0 | | 4+b/-2=-2 | | 0=14d+8d^2 | | (6+y)(2y+5)=0 | | 12x+15=5x+62 | | 5x+x-4=-4 | | 2/3x-1/2y=12 | | (6x-4)-(2x+5)= | | 2/10=b/5 | | Y-12X+4Y+16=0 | | (13a+9b)-(2a-4b)= | | -2(w+4)=2w-24 | | 4y+3=-21 | | 72=9y+36 | | 4(-x-2)+3=15 | | -(-6x+5)=-(x+5) | | (9+7i)/(-10+8i) | | -1+m=-7 | | 3.72x+16=13.8384+4x | | 1/4(2x-3)=7 | | x^4+2x^3-8x=16 | | 16=-4(2x-2) | | b^2+8b-30=3 | | -5/6a=10 | | y=0.14(600)+15.30 | | 1/2/8 |